Psychosocial correlates of mental health of university students in Hong Kong under COVID-19 - Shek, Daniel T. L.; Chai, Wenyu; Dou, Diya; Li, Xiang; Chan, Cathy H. M. (Frontiers in Psychology, 2023)
Although the COVID-19 pandemic has caused many problems for university students, there are several research gaps in the study of psychological well-being of Hong Kong university students. First, few studies have examined different ecological correlates of mental health in a single study. Second, few studies have used both psychological morbidity and positive well-being as indicators of mental health. Third, we know little about the relationships between university students’ perceived need satisfaction, difficulties, service utilization, and their mental health. Hence, we conducted a study (N = 1,020 university students) in the later stage of the COVID-19 pandemic in Hong Kong. For mental health, we included measures of negative mental health (psychological morbidity) and positive mental health. We addressed several research questions in this study: 1) what is the mental health status of Hong Kong university students? 2) what is the relationship between COVID-19 stress and student mental health? 3) what are the intrapersonal correlates of student mental health? 4) are interpersonal factors related to student mental health? 5) are need satisfaction, difficulties encountered, and service utilization related to students’ mental health? 6) are there gender differences in the effects of correlates in different ecological systems? Analyses using structural equation modeling showed several observations. First, the prevalence of mental health symptoms among university students was alarming. Second, COVID-19 related socio-economic stress positively predicted psychological morbidity but negatively predicted well-being. Third, beliefs about adversity, resilience, and emotional competence predicted mental health. Fourth, family functioning was related to psychological morbidity negatively but connected with well-being positively. Fifth, while need satisfaction predicted psychological morbidity negatively, difficulties encountered showed the opposite direction. Besides, the perceived usefulness of university services positively predicted mental health. Finally, there were no gender differences in the effects of different predictors. The present findings enable public health researchers to formulate theoretical models on different ecological determinants of university students’ mental health under the pandemic. For public health practitioners, the study highlights the importance of reducing COVID-19 associated stress, strengthening internal and external developmental assets, and meeting the psychosocial needs of university students as strategies to promote their mental health under the pandemic.